Myśl i praktyka edukacyjna niemieckich pietystów - poglądy i działalność Augusta Hermanna Frankego - Würker, Sylwia (Biuletyn Historii Wychowania, 2008)
The article presents the opinions and pedagogical and educational activity of August Hermann Franke - a person of interesting biography and multifaceted activity. The main objective of this sketch is to demonstrate the influence of the assumptions and practice of Pietists on pedagogical concepts and pragmatic enterprises. As far as the origin and the evolution of Pietists are concerned, the author discusses the common, fundamental assumptions (internalized faith, active social engagement, missionary work aimed at improvement of social conditions) and their exemplifications in the activity of August Hermann Franke. The fundamental conceptions of Franke were based on pietistic motivation for life according to faith and individual experience in working with the youth. The article depicts the functioning of centres and schools founded by Franke, in which the founder introduced progressive teaching and educational methods, promoted an individual approach towards pupils. Also, he maintained strict discipline and a system of reprimand, reproval, threats and punishment. The sketch stresses the significance of teachers’ training for the role of educators and also indicates which assumptions and educational practices of Franke survived until modern-day times.